Cost-effectiveness of different screening strategies for Down syndrome: a real-world analysis in 140,472 women - Jing Liu; Shunyao Wang; Shihao Zhou; Di Ma; Lanping Hu; Hui Huang; Siyuan Linpeng; Jiawei Lin; Liu Hong; Qinmei Fu; Huanhuan Peng; Lijian Zhao; et al. (Frontiers in Public Health)
BackgroundRecent advancements in high-throughput sequencing have validated the accuracy, safety, and effectiveness of non-invasive prenatal testing (NIPT) for Down syndrome (DS).MethodsThis study aims to assess the effectiveness and economic implications of NIPT versus second-trimester serum screening (STSS) for DS and the different screening strategies through retrospectively analyzing data from 140,472 pregnant women who completed both NIPT and STSS (provided for free by local public welfare programs) between March 1, 2018 and December 31, 2020. Data were categorized into eight groups based on different screening strategies.ResultsThe sensitivity, specificity, and positive predictive value of NIPT for detecting trisomy 21 were significantly higher compared with those of STSS. The universal NIPT screening strategy demonstrated the best effectiveness, detecting 163 DS cases with the highest net benefit and a cost-effectiveness ratio of 1:9.53. The STSS and NIPT combined screening strategy detected 128 DS cases with the lowest cost-effectiveness at RMB 341,800. The incremental cost-effectiveness ratio of the universal NIPT screening strategy was RMB 1,186,200, significantly lower than the socioeconomic burden associated with a DS case.ConclusionNIPT demonstrated significantly superior testing performance compared to STSS. At a unit cost of RMB 600, the universal NIPT screening strategy is the most effective and holds substantial health economic value.